Acetylation at Lysine 86 of Escherichia coli HUβ Modulates the DNA-Binding Capability of the Protein - Barlow, Victoria L.; Tsai, Yu-Hsuan (Frontiers in Microbiology, 2022)
DNA-binding protein HU is highly conserved in bacteria and has been implicated in a range of cellular processes and phenotypes. Like eukaryotic histones, HU is subjected to post-translational modifications. Specifically, acetylation of several lysine residues have been reported in both homologs of Escherichia coli HU. Here, we investigated the effect of acetylation at Lys67 and Lys86, located in the DNA binding-loop and interface of E. coli HUβ, respectively. Using the technique of genetic code expansion, homogeneous HUβ(K67ac) and HUβ(K86ac) protein units were obtained. Acetylation at Lys86 seemed to have negligible effects on protein secondary structure and thermal stability. Nevertheless, we found that this site-specific acetylation can regulate DNA binding by the HU homodimer but not the heterodimer. Intriguingly, while Lys86 acetylation reduced the interaction of the HU homodimer with short double-stranded DNA containing a 2-nucleotide gap or nick, it enhanced the interaction with longer DNA fragments and had minimal effect on a short, fully complementary DNA fragment. These results demonstrate the complexity of post-translational modifications in functional regulation, indicating the role of lysine acetylation in tuning bacterial gene transcription and epigenetic regulation.